How do you do this question?
![How do you do this question class=](https://us-static.z-dn.net/files/da1/d45a4412bea5a1ef7ff3ec4d6860d4a1.png)
Answer:
Step-by-step explanation:
[tex]f(x)=sin^2(3-x)\\f'(x)=2 sin(3-x) cos(3-x)(-1)\\f'(0)=-2 sin 3cos 3\\B[/tex]
Answer:
B
Step-by-step explanation:
f(x) = sin^2(3 - x)
f'(x) = 2*sin(3 - x)*cos(3 - x)(-1)
This comes from d(sin^2(3 - x))/dx which is 2*sin^2(3 - x)
d(sin(3 - x)/dx which is cos(3 - x)
d(3 - x) = - 1
f'(0) = (-1) * 2*sin(3)*cos(3)
Looks like B